Funciones desempeñadas como asistente administrativo en el área de recursos humanos de la empresa de Transportes Flor de Higo S.A.C - Orbegoso Carrión, Jorge Luis (2019)
The purpose of this work is to show the work carried out in the company of Transportes Flor de Higo S.A.C. as an accounting assistant for human resources. In the development of my work activities as an accounting assistant in the human resources area of the company Flor de Higo S.A.C. They were focused on the preparation of the return, calculation of salaries and social benefits, payment of life and risk work insurance, liquidation of social benefits, calculation of Compensation for Time of Services, as well as all payments made for labor taxes by electronic payroll with the respective forms defined by SUNAT. The purpose is to show the importance of the work of the accounting profession in the area of human resources that is responsible for everything that has to do with the control and good performance of the staff. This area is of strategic importance because based on its good performance the staff will have a better performance in their work and the company will be more positioned in the market. The development of this report begins with a general description of the company where the work was carried out, in the second chapter the main problems presented during the work performed are analyzed. The third chapter establishes a proposal for a solution to the silver problems. Finally, a critical assessment of the professional accounting and finance career at the National University of Trujillo is established.